IL-6 dependent expansion of inflammatory MDSCs (CD11b+ Gr-1+) promote Th-17 mediated immune response during experimental cerebral malaria. (July 2022) - Mukherjee, Saikat; Ghosh, Soubhik; Sengupta, Anirban; Sarkar, Samrat; Keswani, Tarun; Chatterjee, Rimbik; Bhattacharyya, Arindam
Graphical abstract: Highlights: Myeloid derived suppressor cells (MDSCs) expand in spleen & bone marrow during ECM. MDSCs show increased expression of inflammatory markers during ECM. MDSC depletion increases survival by reducing Th-17 to optimal levels. Expansion and inflammatory changes of splenic MDSCs during ECM depends on IL-6. Abstract: Myeloid derived suppressor cells (MDSCs) are a group of heterogeneous cell populations that can suppress T cell responses. Various aspects of MDSCs in regulating immune responses in several cancer and infectious diseases have been reported till date. But the role and regulation of MDSCs have not been systematically studied in the context of malaria. This study depicts the phenotypic and functional characteristics of splenic MDSCs and how they regulate Th-17 mediated immune response during Experimental Cerebral Malaria (ECM). Flow cytometric analysis reveals that MDSCs in the spleen and bone marrow expand at 8 dpi during ECM. Among subtypes of MDSCs, PMN-MDSCs show significant expansion in the spleen but M-MDSCs remain unaltered. Functional analysis of sorted MDSCs from spleens of Plasmodium berghei ANKA (PbA) infected mice shows suppressive nature of these cells and high production of Nitric oxide (NO). Besides, MDSCs were also found to express various inflammatory markers during ECM suggesting the M1 type phenotype of these cells. In-vivo depletion of MDSCs by the use of Anti Gr-1 increases mice survival but doesn't significantly alter the parasitemia. Previously, it has been reported that Treg/Th-17 balance in the spleen is skewed towards Th-17 during ECM. Depletion of MDSCs was found to regulate Th-17 percentages to homeostatic levels and subvert various inflammatory changes in the spleen. Among different factors, IL-6 was found to play an important role in the expansion of MDSCs and expression of inflammatory markers on MDSCs in a STAT3-dependent manner. These findings provide a unique insight into the role of IL-6 in the expansion of the MDSC population which causes inflammatory changes and increased Th-17 responses during ECM.